Chronic pain among community-dwelling elderly: a population-based clinical study - Susanna Rapo-Pylkkö; Maija Haanpää; Helena Liira (Taylor & Francis Group, 2016)
Objective: To present the occurrence, characteristics, etiology, interference, and medication of chronic pain among the elderly living independently at home. Design/setting: A total of 460 subjects in three cohorts aged 75, 80 and 85 years respectively received visits by communal home-care department nurses for a cross-sectional survey. Of them, 175 had chronic (duration ≥ 3 months) pain with an average intensity of ≥ 4/10 and/or ≥ moderate interference in daily life. Main outcome measures: Clinical assessment was performed for consenting subjects to define the location, intensity, etiology, type, interference and medications of chronic pain. Results: According to home visits, elderly people with chronic pain rated their health and mobility worse and felt sadder, lonelier and more tired than those without chronic pain. A geriatrician made clinical assessments for 106 patients with chronic pain in 2009-2013. Of them, 66 had three, 35 had two and 5 had one pain condition. The worst pain was musculoskeletal in 88 (83%) of patients. Pain was pure nociceptive in 61 (58%), pure neuropathic in 9 (8%), combined nociceptive and neuropathic pain in 34 (32%), and idiopathic in 2 (2%) patients. On a numerical rating scale from 0 to 10, the mean and maximal intensity of the worst pain was 5.7 and 7.7, respectively, while the mean pain interference was 5.9. Mean pain intensity and maximal pain intensity decreased by age. Duration of pain was longer than 5 years in 51 (48%) patients. Regular pain medication was used by 82 (77%) patients, most commonly paracetamol or NSAIDs. Although pain limited the lives of the elderly with chronic pain, they were as satisfied with their lives as those without chronic pain. Conclusions: Elderly people in our study often suffered from chronic pain, mostly musculoskeletal pain, and the origin of pain was neuropathic in up to 40% of these cases. However, elderly people with chronic pain rarely used the medications specifically for neuropathic pain. Based on increased loneliness, sadness and tiredness, as well as decreased subjective health and mobility, the quality of life was decreased among those with chronic pain compared with those without pain. Key Points It is known that chronic pain is one of the most common reasons for general practice consultations and is more common in women than men. In our study using detailed clinical examinations, up to 40% of patients with chronic pain in cohorts aged 75, 80 and 85 years suffered from neuropathic pain. However, only a few elderly people with chronic pain used medications specifically for chronic pain, which may be due to side effects or non-willingness to experiment with these drugs. Elderly people with chronic pain rated their health and mobility to be worse and felt sadder, lonelier and more tired but were not less satisfied with their lives than those without chronic pain.